Inovasi Ramah Lingkungan: Studi Literatur Robot Daisy Apple Inc. dalam Mendukung Daur Ulang Elektronik Berkelanjutan - Ni Wayan Deasi Sastra Astiti; Rahma Sari; Sylvia Emily Binbyak Manpioper; Ulfia Rahma; Nurhayati (Indonesian Journal Publisher, 2026)
This study aims to analyze the role of the Daisy robot developed by Apple Inc. in supporting sustainable electronic waste (e-waste) recycling through a circular economy approach. A literature review methodology was employed by examining academic publications, corporate sustainability reports (2018–2024), patent documents, and global policy reports related to e-waste. The analysis was conducted thematically, covering technical design, environmental innovation, environmental impact, and implementation challenges. The findings indicate that Daisy is capable of disassembling iPhones with high precision while recovering valuable materials such as cobalt, gold, tungsten, and rare earth elements for reintegration into the supply chain. This technology contributes to increased utilization of recycled materials and supports the company’s efforts to reduce greenhouse gas emissions. However, Daisy faces several limitations, including its exclusive focus on iPhone products, substantial investment requirements, and incomplete integration with Design for Disassembly (DfD) principles. Furthermore, concerns have been raised regarding potential greenwashing and the limited global impact of the initiative. Overall, Daisy represents a significant advancement in automated e-waste recycling. Nevertheless, broader integration of sustainable product design and cross-sector collaboration is necessary to achieve scalable and systemic solutions.